Implementation of Sustainability Mindset in MSMEs-A Qualitative Study - Annisa Yumna Ulfah; Ida Ariyani; Arie Wibowo Khurniawan (Publikasi Indonesia, 2024)
A mindset based on Sustainability principles can guide MSME managers to move towards transformative changes that can minimize risks such as landfilling, and realize the linkage between business and business carried out with the surrounding environment. The qualitative research was conducted by interview and direct observation methods on the owners of Güzel Dish MSMEs located in East Kotawaringin, Central Kalimantan with guidance from the Sustainability Mindset Indicator by Isabel Rimanoczy. The research found that Güzel Dish's MSME managers have partially implemented indicators of a sustainable mindset